1985
DOI: 10.1126/science.230.4728.961
|View full text |Cite
|
Sign up to set email alerts
|

Response : Neuroendocrine Response to Estrogen and Sexual Orientation

Abstract: marmosets (4), estradiol stimulated similar increments in serum LH concentrations in both males and females, provided the animals were gonadectomized at the time estrogen was given. No such estrogen-induced surge in LH was seen in male macaques with gonads (5). Daily intramuscular injections of 1.5 mg of estradiol benzoate (EB) into four castrated men of unspecified sexual orientation caused a significant depression in serum LH, followed by a significant surge in LH secretion 120 hours after the onset of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
9
0
3
Order By: Relevance
“…Following evidence of an F/dM pattern of LH surges in response to estradiol injections among many male rats who had had their sexual orientations experi-mentally inverted (Dorner, 1967(Dorner, , 1972Kalcheim et ah, 1981), Dorner, Rohde, Stahl, Krell, and Masuis (1975) reported similar tendencies in about one-half of a group of human male homosexuals. More recently, Gladue, Green, and Hellman (1984) also found that about one-half of the male homosexuals they tested exhibited an LH surge in response to estradiol injections, something that was found in almost no male heterosexuals.…”
Section: Homosexuals Should Have Higher Frequencies Of Other Sexualmentioning
confidence: 93%
“…Following evidence of an F/dM pattern of LH surges in response to estradiol injections among many male rats who had had their sexual orientations experi-mentally inverted (Dorner, 1967(Dorner, , 1972Kalcheim et ah, 1981), Dorner, Rohde, Stahl, Krell, and Masuis (1975) reported similar tendencies in about one-half of a group of human male homosexuals. More recently, Gladue, Green, and Hellman (1984) also found that about one-half of the male homosexuals they tested exhibited an LH surge in response to estradiol injections, something that was found in almost no male heterosexuals.…”
Section: Homosexuals Should Have Higher Frequencies Of Other Sexualmentioning
confidence: 93%
“…Therefore, we propose that the fundamental organization/activation theory of steroid hormone action, [that steroids bind to nuclear receptors during development and adulthood to shape neural/behavioral phenotypes (Phoenix et al, 1959;Arnold and Breedlove, 1985;Emerson, 2000)], can be expanded to include the rapid actions of steroid hormones on the neurophysiological mechanisms of adult behavior. Comparable steroid mechanisms may explain the widespread distribution of divergent neural/behavioral patterns among teleosts with ARTs, as well as the many examples of intrasexual divergence in behavioral phenotypes among tetrapods (Rhen and Crews, 2002;Roselli et al, 2004), including humans and other primates (Gladue et al, 1984;Maggioncalda et al, 2002;Morris et al, 2004). The androgen receptor antagonist CA eliminates the rapid effects of androgens in type I and type II males, but not females, whereas the aromatase inhibitor FAD blocks the rapid effects of androgens in females but not type I and type II males.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…This perspective may have important implications for the atypical neuroendocrine phenotypes associated with intrasexual divergence in social behavior among tetrapods (Rhen and Crews 2002;Roselli et al, 2004), including humans and other primates (Gladue et al, 1984;Maggioncalda et al, 2002;Morris et al, 2004). Divergent androgen mechanisms on CPGs may be particularly important, since the rapid actions of 11kT and testosterone appear to be highly steroid-specific in midshipman (Remage-Healey and Bass, 2007).…”
Section: Concluding Commentsmentioning
confidence: 99%